How young people learn public participation – from the family to the public sphere - Achremowicz, Hanna (EDUsfera. Ewa Jurczyk-Romanowska, 2020)
Public participation is an important element of modern democracy. One of the important challenges of pedagogy and family upbringing is to answer the question: what is the best way to prepare young citizens to be active in public life?
Keywords: public participation; youth; learning; family; democracy